2008
DOI: 10.1002/mds.22098
|View full text |Cite
|
Sign up to set email alerts
|

[123I]FP‐CIT SPET imaging in drug‐induced Parkinsonism

Abstract: We assessed the status of dopamine nerve terminals in patients treated with dopamine receptor blocking agents (DRBAs) who had developed drug-induced parkinsonism (DIP). We performed [(123)I]FP-CIT SPET in 32 consecutive patients who were on DRBAs for at least 6 months and developed extrapyramidal signs. The UPDRS-III was used to assess clinical severity. Twenty-six age- and sex-matched healthy subjects served as control group. Putamen [(123)I]FP-CIT SPET binding was reduced in 14 and normal in the remaining 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 24 publications
1
36
0
1
Order By: Relevance
“…However, in both studies, the functional integrity of the dopaminergic nigrostriatal pathway has not been directly assessed. This is a crucial aspect, considering that recently, this study and others, using [ 123 I] FP-CIT SPECT, demonstrated that about 42-55% of DIP patients present significant putamen dopamine transporter (DAT) binding abnormalities, consistent with loss of dopamine nerve terminals [16,17]. It has been suggested that the presence of normal [ 123 I] FP-CIT binding may be consistent with DIP induced by the blockade of D2 receptors, while the presence of putamen uptake abnormalities in DIP may be associated with progressive degenerative parkinsonism [16,17].…”
Section: Introductionmentioning
confidence: 96%
“…However, in both studies, the functional integrity of the dopaminergic nigrostriatal pathway has not been directly assessed. This is a crucial aspect, considering that recently, this study and others, using [ 123 I] FP-CIT SPECT, demonstrated that about 42-55% of DIP patients present significant putamen dopamine transporter (DAT) binding abnormalities, consistent with loss of dopamine nerve terminals [16,17]. It has been suggested that the presence of normal [ 123 I] FP-CIT binding may be consistent with DIP induced by the blockade of D2 receptors, while the presence of putamen uptake abnormalities in DIP may be associated with progressive degenerative parkinsonism [16,17].…”
Section: Introductionmentioning
confidence: 96%
“…Such a drug-exacerbated parkinsonism may represent patients at a prodromal state of PD who do not tolerate the offending medication. Furthermore, it has concordantly been reported that in patients suspected of having drug-induced PS who, however, presented with pathologic DAT binding, either neurodegenerative PS alone or a combination of neurodegenerative and drug-induced PS was finally determined to be present (45,(59)(60)(61).…”
Section: Drug-induced Psmentioning
confidence: 66%
“…It binds the dopamine transporter (DAT), a protein expressed exclusively in dopaminergic neurons (Varrone and Halldin 2010). The main clinical use of DAT-SPECT is for quantification of dopaminergic deficits in PD, assisting in discrimination of pre-synaptic from postsynaptic parkinsonism (Tinazzi et al 2008). In early PD patients, we observed an association of the rs12678719 AIP risk allele "G" with decreased ligand uptake in the contralateral putamen when controlling for disease duration.…”
Section: Discussionmentioning
confidence: 93%
“…These provisional findings provide proof of concept for our exploratory hypothesis about the possible effect of AIP variants on the NS system. Interestingly, several neuroimaging studies in drug-induced parkinsonism patients unexpectedly revealed that large portion of them suffer from significantly diminished striatal binding in DAT scans (Burn and Brooks 1993;Lorberboym et al 2006;Tinazzi et al 2008;Tinazzi et al 2009). Therefore, at least in a subgroup of AIP patients, both pre-and post-synaptic mechanisms might be involved in their parkinsonism.…”
Section: Discussionmentioning
confidence: 96%